Pelatihan Kader Sebagai Agen Promosi Kesehatan Pencegahan Kekerasan Seksual pada Anak - Mindarsih, Eko; Masruroh, Masruroh; Setyaningsih, Dewi; Solihin, Muhammad (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
The objective of this community service is to improve the knowledge and skills of health cadres on preventing sexual violence against children. The method of implementing this service uses Focus Group Discussion (FGD) targeting mothers of cadres in Plumbon Village, Temon District, Kulon Progo. The evaluation instrument for this service uses pre-test and post-test questionnaires which are then analyzed using percentage techniques. The results of the pre-test showed that 76% were able to answer all questions correctly. After providing material and FGD on the concept and prevention of sexual violence against children, the results of the post-test of community service participants who answered correctly increased by 12% or to 88% of participants with correct answers. So it can be concluded that there is an increase in the knowledge of mothers of health cadres in Plumbon Village about preventing sexual violence against children, as one of the provisions for carrying out health promotion.